1995
DOI: 10.1097/00000542-199502000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Dose-Response Relationship of Tranexamic Acid 

Abstract: Prophylactic tranexamic acid, 10 mg.kg-1 followed by 1 mg.kg-1.h-1, decreases bleeding after extracorporeal circulation. Larger doses do not provide additional hemostatic benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
8

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(94 citation statements)
references
References 40 publications
3
83
0
8
Order By: Relevance
“…Previous studies have shown no significant difference in mortality benefit between low and high doses of TXA 29,30. In emergency situations, a fixed one-gram dose followed by a one-gram maintenance dose (if a patient continued to satisfy inclusion criteria), has been deemed most practical 12.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown no significant difference in mortality benefit between low and high doses of TXA 29,30. In emergency situations, a fixed one-gram dose followed by a one-gram maintenance dose (if a patient continued to satisfy inclusion criteria), has been deemed most practical 12.…”
Section: Discussionmentioning
confidence: 99%
“…13 The dose-response relationship of TXA was examined by Horrow et al, 14 who concluded that 10 mg/kg followed by 1 mg/kg/hour decreases bleeding after extracorporeal circulation and that larger doses did not provide any additional haemostatic benefit.…”
Section: Dose Selectionmentioning
confidence: 99%
“…Studies in cardiac surgery have noted that a 10 mg/kg-loading dose of TXA followed by an infusion of 1 mg/kg/hour produces plasma concentrations sufficient to inhibit fibrinolysis, and that a larger dose does not provide any additional haemostatic benefit. 13,14 In emergency situations, the administration of a fixed dose is practicable since determining the weight of a seriously injured patient can be difficult. We therefore selected a fixed dose within the range shown to inhibit fibrinolysis and provide haemostatic benefit that would be efficacious for larger patients (> 100 kg) but also safe in smaller patients (< 50 kg), to the extent that the dose per kg that smaller patients would receive has been used in surgical trials without adverse effects.…”
Section: One-way Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The first was to define an appropriate effective dose. There is only one study investigating a dose-response relationship [3]. This article showed a plateau effect on drains losses with a total dose of 3 grams tranexamic acid but with no observed effect on transfusions.…”
mentioning
confidence: 98%